FAKTOR-FAKTOR YANG MEMPENGARUHI PERSISTENSI LABA - Wahyuni, Sri; Bangun, Nurainun (Jurnal Paradigma Akuntansi, 2025)
The purpose of this study was to determine the effect of accruals, sales volatility, and managerial ownership on earnings persistence in companies in the basic and chemical industries, various industries, and consumer goods listed on the Indonesia Stock Exchange (IDX) for the 2018–2020 period. This study used a sample of 31 companies selected using purposive sampling and used the Eviews 12.0 application to process the data. The results showed that the independent variables affected earnings persistence simultaneously (F test). The results of the T test indicate that the sales volatility variable has a significant effect on earnings persistence. Meanwhile, accruals and managerial ownership variables have no significant effect on earnings persistence. The implication in this study is that high sales volatility will cause profit persistence to increase because sales are one of the most important activities in generating profits.